Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 1 - Limits and Their Properties - 1.5 Exercises: 22


Vertical asymptote at $x=1$ and at $x=-1.$

Work Step by Step

$h(x)=\dfrac{x^2-9}{x^3+3x^2-x-3}=\dfrac{(x+3)(x-3)}{(x+3)(x-1)(x+1)}$ $=\dfrac{x-3}{(x-1)(x+1)}.$ Vertical asymptotes occur when the denominator alone is $0\to$ $(x-1)(x+1)=0\to x=1$ or $x=-1.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.